Obstacles to administrative innovation in the secondary school principals in the city of Tabuk - Al Hadrami, Nouf Bint Khalaf; Al Shawamin, Basma Ibrahim (Journal of Educational and Psychological Sciences, 2017)
The study aimed at identifying the organizational, personal, cultural and social constraints of the administrative creativity of the secondary school principals in Tabuk city. To achieve the objectives of the study, the researcher used the descriptive approach and the researcher adopted the questionnaire to collect the data.A sample of 32 managers was selected.1. Obtained the administrative obstacles of the principals of secondary schools in the city of Tabuk on the average (24.2) grade (medium) and at the level of areas; organizational constraints obtained an average of 2.22. Ie, to a moderate degree, while the personal obstacles obtained an average of (2.30). As well as social obstacles averaged (2.19). All of which are estimated (medium).2. There were no statistically significant differences between the responses of the sample of the study sample on the obstacles of administrative creativity in the secondary school principals in Tabuk due to the variable number of years of service.In light of the results of the study, the researcher recommended the creation of a specialized department in the Department of Education concerned with creative and creative subjects. And intensifying training courses for secondary school principals and administrative leaders in the field of administrative innovation.
Keywords: organizational obstacles; personal obstacles; cultural and social obstacles